REACTION OF THE POPULATION OF BERAN NAHIYA TO THE ANNEXATION OF BOSNIA AND HERZEGOVINA (Heritage, 2020)
On 7th October,1908, Austro-Hungary executed an annexation of Bosnia and Herzegovina. This act of Austro-Hungary caused a great diturbance among the inhabitants of Novopazar sandzak. Serbs joined Turkish and Albanians at protest rallies and boycott of Austro-Hungarian goods. It made an impressioin that closer cooperation could  be made, even the union betveen Serbs and Muslim - Albanian leaders. Austro-Hungary was especially afraid of common appearances of Orthodox and Muslims, supporters of young Turkish authorities against the annextion of Bosnia and Herzegovina.Therefore Austro-Hungary endeavoured to destabilize this area,encouraging the hate between Christians and Mohammedans.        In Sjenica, on 19th October (1st November), 1908, an assembly took part, which was attended  by  the representatives of Orthodox and Mohammedan people from Novopazar sandzak. Serbs were represented by 27 deputies from Donji Vasojevići, Pljevlja and Bijelo Polje. Many of deputies made a speech on the assembly, and among the speakers the representatives of Serbs from Donji Vasojevići were prominent. Only three days after the assembly in Sjenica, the public choir was organized at Đurđevi Stupovi in Berane. On this choir  which took part on 22nds October (4th november), 1908, the assembled people from sjenica,Novi Pazar, Nova Varoš, Prijepolje, Bijelo Polje, Rožaje and Berane condemned the annexation of Bosnia and Herzegovina once again. On the assembly, where about 3000 Orthodox and Mohammedan inhabitants took part together, they chose the joint Committee of Serbs and Turks for planned action against Austro-Hungarian violence in Bosnia and Herzegovina. At the end,this shameful act of violence that Austro-Hungary had done, was condemned by resolution and the potest was sent to European forces because they allowed one violent state to break Berlin Contract,and also demand for not allowing Austro-Hungary to “grab someone else’s land and oppress other nations”.        Serbia and Montenegro were trying to acquire Constantinople for trinomial Millitary Alliance.They tended to make Military convention wsith Turkey and they were ready to pay the compensation for concession of Sandzak.however,the three states didn’t make an alliance.Beside the declarative condemnation of annexation, Turkey didn’t have enough determination for armed opposing to Austro-Hungary.In whole Turkey, especially in Sandzak, among Mohammedan population, there was the suspicion toward intentions of Belgrade and Cetinje. The solidarity of Orthodox and Muslim population existed only at the beginning of annexation crisis, and later it started to disappear. Turkish hypocritical politiciansnegotiated simultaneouslz with Austro- Hungary,too.Thus,on 26th February, Turkey officially admited  the annexation of Bosnia and Herzegovina, and in that way struck a death blow to Serbo-Montenegrian hopes. Since Russia, according to European “March ultimatum, also admited the annexation in March, 1909, Serbian Government didn’t have the choice, so they did the same on 31st March, 1909. Five days later (on 5th April), Montenegro also admited the annexation of Bosnia and Herzegovina. By these admissions, an annexation crisis calmed down, but the dissatisfaction of the entire Serbian population was still great.
Keywords: annexation, Bosnia and Herzegovina, Austro-Hungary, Serbia, Montenrgro, Turkey, Berane, Novopazar sandzak, Serbian people